Bergmann′s rule in mammals: a cross‐species interspecific pattern. Issue 10 (19th March 2013) - Clauss, Marcus; Dittmann, Marie T.; Müller, Dennis W. H.; Meloro, Carlo; Codron, Daryl
Abstract : Although Bergmann's rule – stating that among closely related species, the bigger ones will inhabit the colder climates/higher latitudes – was formulated for inter‐specific comparisons, most analyses that tested this pattern in mammals were on an intra‐specific level. To date, no large‐scale taxonomy‐driven cross‐species evaluation of the pattern predicted by Bergmann exists. Here we show, in a dataset comprising 3561 mammal species from 26 orders, that while there is no significant correlation between latitude and body mass using conventional methods, this correlation is highly significant when the phylogenetic structure of the dataset is accounted for, thus supporting Bergmann's claim that the rule only applies to closely related species. Analyses of different subsets indicate that the Bergmann's rule is evident across a variety of latitude ranges. In many taxonomic subsets, when analysed alone, there is no significant correlation between body mass and latitude. In combination with both the significant relationship in the overall dataset and with results of intra‐specific analyses from the literature, this suggests that Bergmann's rule describes a fundamental principle within mammals, but that its expression has been modified by a variety of factors during mammalian diversification yet to be resolved.